MENGUNGKAP PESAN-PESAN AL-QURAN MELALUI PETUAH BUGIS PAPPASENG TO RIYOLO - Sugirma Sugirma (Institut Agama Islam Negeri Palopo, 2017)
Pappaseng is an oral literature spoken by to riyolo na Ugi'e (ancestor of the Bugis tribe) to give a message to ana 'monri'e (young generation) so as not to fall into the things that are not desirable. While the Quran is a holy book for Muslims that contains values from all aspects of human life, including the one is about moral messages, ethics and rule of interaction. Both become the basis of life of Bugis tribe people in living their lives and interact with each other. this research is a qualitative research with a cultural approach to search for The Quran relationship with the advice Bugis pappaseng form as a repertoire of science in the Bugis society. And obtained the result that the value contained in pappaseng always connected directly with the content of the Quran, such as courage, honesty, work ethic of faith and so forth.